Pendekatan Pastoral dalam Pendidikan Karakter Kristen Generasi Z berdasarkan Amsal 22:6 - Sutarman Laia; Nehemia Nome (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
This article discusses the role of pastoral counseling in shaping the character of Christian Generation Z, focusing on the exposition of Proverbs 22:6 as a biblical foundation. The research background stems from the challenges faced by Generation Z in the fast-paced digital era, which necessitates a relevant spiritual guidance approach. The research problem addresses how pastoral counseling can serve as an effective tool in guiding Generation Z to uphold Christian values. This study employs a qualitative method based on literature research, examining relevant works on the concept of pastoral counseling and the exposition of Proverbs 22:6. The aim of the research is to identify the relevance of pastoral counseling in the context of faith formation for Generation Z. The novelty of this research lies in its biblical exposition approach, specifically linked to Generation Z and the challenges of the digital age. The research findings suggest that pastoral counseling, grounded in the principles of Proverbs 22:6, can help Generation Z develop strong Christian character through relevant and contextual approaches.